IoT based System for Air Pollution Monitoring in Banda Aceh - Roslidar Roslidar; Karnaini Karnaini; Teuku Yuliar Arif (Universitas Syiah Kuala, 2023)
Air pollution is a factor that affects the clear skies and breathable air of the city. Humans cannot directly quantify the changes in air quality; hence we need a technological tool to detect the changes in air quality around them. This study proposed a prototype to monitor air quality using embedded system hardware of Arduino Uno-R4 and ESP8266. A Thingspeak database is used as a platform for data communication between smartphones and sensors in real time. The data is retrieved once every 15 seconds. In this prototype, the Arduino Uno-R3 is used as the main brain of the system to connect to WiFi communication via ESP8266 and to four (4) sensors, namely CO (MQ-7), CO2 (MQ-9), dust (PM10), and DHT22 (temperature and humidity). The developed prototype is portable and has low power consumption. Several testing locations have been identified to monitor the air pollution; (1) Simpang Lima Intersection and (2) Jeulingke Bus Stop in Banda Aceh. The system performance shows the connectivity between devices has only a delay of ± 1.1 seconds; therefore, the system is suitable for real-time usage.